2020
DOI: 10.5194/soil-2020-50
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global concentrations of microplastic in soils, a review

Abstract: Abstract. Worldwide, microplastic (MP) has been commonly recognized as a threat for soil ecosystems. Terrestrial soils are widely contaminated by MP due to the application of sewage sludge and wastewater, plastic mulching, littering, the input of tire wear from roads and atmospheric deposition. Within the last decade, an increasing number of individual studies focused on item counts and masses of MP in different global soil environments. We reviewed these studies to achieve a representative picture of common d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The potential consequences of ecological surprise are especially acute in terrestrial agroecosystems, given their role in providing the vast majority of the human food supply. Current agricultural practices, plastic mulching and the application sewage sludge as fertilizers, are considered as major entry routes for microplastics into terrestrial ecosystems (Büks & Kaupenjohann, 2020; Corradini et al, 2019; Nizzetto et al, 2016). However, microplastics do not occur in isolation; other environmental pressures resulting from natural disturbances, for example, drought, flood and pest infestation (Food & Agriculture Organisation, 2017), anthropogenic activities, for example, global warming (Gornall et al, 2010), pesticide use (Aktar et al, 2009), invasive species (Paini et al, 2016) and heavy metal contamination (Li et al, 2019) also occur in agroecosystems.…”
Section: The Need To Move Toward Ecological Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential consequences of ecological surprise are especially acute in terrestrial agroecosystems, given their role in providing the vast majority of the human food supply. Current agricultural practices, plastic mulching and the application sewage sludge as fertilizers, are considered as major entry routes for microplastics into terrestrial ecosystems (Büks & Kaupenjohann, 2020; Corradini et al, 2019; Nizzetto et al, 2016). However, microplastics do not occur in isolation; other environmental pressures resulting from natural disturbances, for example, drought, flood and pest infestation (Food & Agriculture Organisation, 2017), anthropogenic activities, for example, global warming (Gornall et al, 2010), pesticide use (Aktar et al, 2009), invasive species (Paini et al, 2016) and heavy metal contamination (Li et al, 2019) also occur in agroecosystems.…”
Section: The Need To Move Toward Ecological Studiesmentioning
confidence: 99%
“…Since then, attention has spread to freshwater (de Sá et al, 2018; Hoffman & Hittinger, 2017; Li et al, 2018) and terrestrial environments (de Souza Machado, Kloas, et al, 2018; Rillig & Lehmann, 2020; Windsor et al, 2019). Microplastic research in the terrestrial environment is still at an early stage, despite multiple lines of evidence indicating terrestrial systems as the major sinks of microplastics (Büks & Kaupenjohann, 2020; Evangeliou et al, 2020; Nizzetto et al, 2016). The development of terrestrial microplastics research has followed a similar trajectory to work on aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that almost every environmental compartment on earth is contaminated with plastic (Howell et al 2012;Bergmann et al 2017;Horton et al 2017a;Hendrickson et al 2018;Büks and Kaupenjohann 2020). The majority of research to date has focussed on aquatic, particularly marine, environments, whereas the occurrence of microplastics in soils has only recently started to generate research interest.…”
Section: Introductionmentioning
confidence: 99%
“…For example, negative impacts on survival (Huerta Lwanga et al 2016;Cao et al 2017), biomass (Cao et al 2017;Zhu et al 2018a;Boots et al 2019) and reproduction (Zhu et al 2018a;Kim et al 2019) have been reported for terrestrial species including earthworms (Eisenia fetida, Eisenia andrei, Lumbricus terrestris), collembola (Folsomia candida) and nematodes (Caenorhabditis elegans). The exposure doses used in many studies likely represent 'worst-case scenario' environmental concentrations, although direct comparisons are uncertain owing to a relative scarcity of environmental concentration data and inconsistencies in how such data are reported (Büks and Kaupenjohann 2020). Some of these negative effects likely arise from the physical damage caused by the microplastic particles to dermal surfaces or within the organism itself.…”
Section: Introductionmentioning
confidence: 99%